Chemical genetics to examine cellulose biosynthesis - Debolt, Seth; Brabham, Chad (Frontiers in Plant Science, 2013)
Long-term efforts to decode plant cellulose biosynthesis via molecular genetics and biochemical strategies are being enhanced by the ever-expanding scale of omics technologies. An alternative approach to consider are the prospects for inducing change in plant metabolism using exogenously supplied chemical ligands. Cellulose biosynthesis inhibitors (CBI) have been identified among known herbicides, during diverse combinatorial chemical libraries screens, and natural chemical screens from microbial agents. In this review, we summarize the current knowledge of the inhibitory effects of CBIs and further group them by how they influence fluorescently tagged cellulose synthase A (CESA) proteins. Additional attention is paid to the continuing development of the CBI toolbox to explore the cell biology and genetic mechanisms underpinning effector molecule activity.